Vegetarian diet for exercise and athletic training and performing: An update - Larson, D. E. (Issues in Vegetarian Dietetics, 1997)
Fruitarian and strict macrobiotic diets) can easily meet the nutritional requirements of all types of athletes provided they contain a variety of plant-foods. Vegetarian athletes, like most athletes, may benefit from education on food choices that benefit athletic performance and promote overall health. Nutritionists can play an essential role optimizing the health and athletic performance of vegetarian athletes of all ages and abilities. Sports nutritionists who work with vegetarian athletes and their coaches and trainers, however, need to be sensitive to and knowledgeable about vegetarian issues. In this setting, the role of the nutritionist is to work with the athlete to ensure adequate nutritional status given his/her vegetarian beliefs, income and lifestyle. While athletes should be encouraged to eat a wide variety of plant foods, this does not mean convincing the vegetarian athlete that they need poultry, fish or dairy products in the diet. The American Dietetic Association's position on vegetarian diets states that "vegetarian diets are healthy and nutritionally adequate when appropriately planned" (90).